Where Does the Public Sector End and the Private Sector Begin? - Lienert, Ian (IMF Working Papers; Working Paper ;, 2009)
The boundary between the public and private sectors can be defined on the basis of ownership of institutional units. Nonmarket government-owned entities and corporations that are owned or controlled by government units belong to the public sector. 'Economic ownership' is more important than majority ownership. Joint ventures, public-private partnerships, and social insurance funds (including for public employees) can be unambiguously allocated to the public or private sector on the basis of international public sector accounting standards. Boundary problems within the public sector are just as acute as those between the public and private sectors, mainly because of ambiguities in distinguishing 'market' from 'nonmarket' activities.